2010
DOI: 10.1002/cncr.25220
|View full text |Cite
|
Sign up to set email alerts
|

Overexpressed epidermal growth factor receptor (EGFR)‐induced progestin insensitivity in human endometrial carcinoma cells by the EGFR/mitogen‐activated protein kinase signaling pathway

Abstract: BACKGROUND: Fertility-sparing management is an important treatment for young women who have endometrial carcinoma (EC). Many patients with EC exhibit insensitivity or resistance to progestin therapy, and the molecular mechanisms of that insensitivity and resistance have been elusive. Epidermal growth factor receptor (EGFR) overexpression has been observed in EC, but the roles of EGFR in progestin resistance have not been investigated. METHODS: EGFR and progesterone receptor isotype B (PR-B) messenger RNA and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 27 publications
1
23
0
Order By: Relevance
“…The results are in agreement with those of Hipp et al (2009) who showed regulation of SNAIL by activation of EGFR via Akt and ERK1/2 pathways in Ishikawa cells. Activation of EGFR/MAPK pathway via overexpression of EGFR and its contribution to reduced PR-B expression and increased progestin resistance in EC has been reported (Ai et al 2010).…”
Section: Cell Signaling Pathwaysmentioning
confidence: 98%
“…The results are in agreement with those of Hipp et al (2009) who showed regulation of SNAIL by activation of EGFR via Akt and ERK1/2 pathways in Ishikawa cells. Activation of EGFR/MAPK pathway via overexpression of EGFR and its contribution to reduced PR-B expression and increased progestin resistance in EC has been reported (Ai et al 2010).…”
Section: Cell Signaling Pathwaysmentioning
confidence: 98%
“…Potential therapeutic targets for HNSCC, including epidermal growth factor receptor (EGFR), have been researched over the past decade. High EGFR expression is associated with poor prognosis in head and neck squamous-cell carcinoma and with resistance to radiotherapy (10,11). A previous study demonstrated that nimotuzumab combined with radiotherapy or chemotherapy was associated with improved locoregional tumor control and survival compared with standard chemoradiotherapy in patients with locally advanced HNSCC (12).…”
Section: Introductionmentioning
confidence: 99%
“…When further EGFR expression was stimulated in Ishikawa cells, the susceptibility to progestin decreased, accompanied by reduction in PRB expression. AG1478 (a specific inhibitor for EGFR tyrosine kinase) effectively suppressed the proliferation of EGFR-overexpressed endometrial cancer cells (45). On the basis of these findings, we may say that excessive expression of EGFR in endometrial cancer cells can reduce the susceptibility to progestin therapy.…”
Section: Progestin Therapy For Endometrial Cancermentioning
confidence: 90%